A survey on the feeding of competition horses and perceptions of forage in the UK and Sweden - Hurtes, Auriane (2015)
Classical feeding practices of the performance horse have included the necessity for energydense concentrates that are rich in starch in order to meet its’ high energy requirements. Such diets have been associated to numerous health problems. Moreover, access to forage is traditionally limited due to time constraints and perceptions of it hindering athletic performance. The aim of the present study was to assess the current feeding practices and perception of forage within the competition industry. This was done through an online survey for harness racing trainers and elite level 3-day event riders in the UK and Sweden. Results indicated that feeding practices varied between the disciplines and countries. Hay (45%) and haylage (42%) were the main forages fed. Respondents fed on average 3.6 kg of concentrates daily and most reported turning out their horses on pasture. Less concentrate and more forage was fed in Sweden compared to the UK (p<0.001). Health was selected as the most important factor determining their horses’ feed, more so than performance. Most respondents reported a nutritionist was their main source of nutritional advice. Perceptions of forage in the UK reflected the traditional view that forage cannot meet the high energy requirements of the athletic horse. On the other hand, perceptions of forage in Sweden reflected the findings of research. Overall, respondents were open-minded to a forage-only diet for their athletic horses.